Location genealogic of Expert Psychology in judicial system: ethical implications - Costa Beber Brunini, Barbara Cossettin [UNESP]; Benelli, Silvio Jose [UNESP] (Univ Autonoma Barcelona, Dept Psicologia Salut, 2016)
This work is an essay from the writings of our Master's thesis in Psychology and Society of UNESP / Assis, who intends to problematize the interfaces present in the relationship between psychology and law when inserting the professional psi in judicialized environments acting as agent court in accordance with the provisions of Criminal procedure Code. The methodology chosen for us is the Foucault's genealogy, finding the writings and reflections of Michel Foucault, directions to the problematizations for us proposals on the ethical implications of the subject expert psychologist. The relations of power-knowledge that cross professional doings, the power of the watchful eye that regulates the docile behavior, examination as expected activity of professional psi as evidence in support of the decision-making process of the judge, all mechanisms of orthopedics displayed in interventions still played by psychologists that emerge in these legal areas.
Keywords: Legal Psychology; Expert; Ethical Implications